Education, Regulation, and Public Administration - Suprianto Suprianto (ASHA Publishing, 2024)
This article explores the intricate relationships among education, regulation, and public administration, highlighting how these three domains collectively shape the effectiveness of governance and societal development. Using a qualitative-descriptive approach, the study draws upon relevant global literature and case examples to examine the regulatory frameworks that govern education and their influence on public administration outcomes. The findings emphasize that educational policy reform, when aligned with public service goals and robust administrative frameworks, can enhance efficiency, equity, and quality in public service delivery. Furthermore, the article underscores the importance of continuous training and development for public administrators to ensure policy responsiveness in a rapidly globalizing world. Theoretical contributions include a deeper understanding of transnational policy diffusion and its local adaptation in public administration, while practical implications point toward the need for integrated governance models that connect educational standards with regulatory effectiveness. This article contributes to the ongoing discourse on how interdisciplinary policy frameworks can address modern governance challenges in both developed and developing nations.